Revealing the role of the AGO4 gene against rice hoja blanca virus: from transformation to protein structure - Ñañez, Johan; Valdes, Sandra; Cruz Gallego, Maribel; Rebolledo, Maria Camila; Lorieux, Mathias; Alvarez, Maria Fernanda; Chavarriaga, Paul (Frontiers in Plant Science, 2025)
Rice hoja blanca virus (RHBV), transmitted by the insect vector Tagosodes orizicolus, poses a significant threat to rice cultivation. Here, we use CRISPR/Cas9 technology to produce specific mutations in the AGO4 gene of Oryza sativa, using the Fedearroz 2000 variety, with the aim of elucidating the participation of the gene in resistance to RHBV. We obtained 14 edited plants that presented with deletions of one, two, and three nucleotides in the sequence of exon 23 of the AGO4 gene. Phenotypic evaluations showed an increase in susceptibility to RHBV in the edited lines. We identified the presence of RHBV in the leaf tissue of infected plants by amplifying the nucleoprotein, NS3, and NS4 genes of the virus. Using RT-qPCR, we analyzed the expression patterns of the AGO4 gene, showing that in the edited lines, the expression profiles are similar to the susceptible control. Furthermore, modeling of the tertiary structure of the AGO4 protein and its mutant variant demonstrated changes in the PIWI domain and the presence of the DDH catalytic triad, confirming its role in mediating resistance to RHBV. Our study reveals the functional importance of the rice AGO4 gene in RHBV resistance.